Urine cortisol and cortisone and water intake in athletes - Gatti, R.; Antonelli, G.; Zecchin, B.; Spinella, P.; Mantero, F.; de Palo, E. F. (The Journal of Sports Medicine and Physical Fitness, 2008)
Aim. The aim of this study was to investigate the urine cortisol (F) and cortisone (E) relation, having a well-defined water intake. Methods. Urine specimens were collected from 10 male trained cyclists (19±1 year, 70±4 kg, 179±4 cm), at rest just before the test (pre-exe) and until 45 min after the cycle ergometer exercise test (45 min at 50-60% V.O2max) (post-exe) in the morning. This investigation measured the diuresis in the pre-exe and post-exe after each athlete had drunk 1 L of water from waking-up, after bladder emptying, to the start of the test (pre-exe) and 1 L during the 45 min after the exercise (post-exe). Results. Urinary F and E concentrations demonstrated a significant decrease comparing pre-exe with post-exe (177±134 vs 64±21 and 706±475 vs 372±178 nmol/L respectively, p<0.05). This significant decrease was verified when diuresis and urinary creatinine were taken into account and the ratio measured. Conclusion. One litre of water intake after exercise seemed to have no effect on urine F and E excretion. Moreover the urine F/E ratio was not statistically different comparing pre-exe with post-exe.